ERGONOMIC WORKING ENVIRONMENT TO IMPROVE WORKFORCE HEALTH - Gempur Santoso (International Journal of Social Science, 2026)
In work that can produce good work productivity, the work environment must be arranged that is ergonomic so that the workforce at work is always healthy. All data is taken from various opinions of ergonomists and research results, it is commonly referred to as a literature study. Then, the analysis is also carried out descriptively or presentation. Ambiguity: Based on the above discussion, it can be concluded as follows that the company's environment must be clean, namely an environment that does not deviate from the threshold value and the quality standard value. These values are the physical environment, chemical environment, and biological environment. In addition, it is also an environment related to psychology. Suggestion: It is recommended for companies that their company must be maintained so that it remains clean according to the threshold value and quality standards of a healthy and safe stand-up workforce